2017
DOI: 10.1038/srep39759
|View full text |Cite
|
Sign up to set email alerts
|

Study on relationship between pollen exine ornamentation pattern and germplasm evolution in flowering crabapple

Abstract: Pollen ornamentation patterns are important in the study of plant genetic evolution and systematic taxonomy. However, they are normally difficult to quantify. Based on observations of pollen exine ornamentation characteristics of 128 flowering crabapple germplasms (44 natural species and 84 varieties), three qualitative variables with binary properties (Xi: regularity of pollen exine ornamentation; Yi: scope of ornamentation arrangement regularity; Zi: ornamentation arrangement patterns) were extracted to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Pollen ornamentation is one of the most significant characteristics that can be used to separate taxa (Pınar et al, 2009;Mačukanović-Jocić et al, 2017;Zhang et al, 2017). We observed that Scaligeria was striate, striate-rugulate, striate-reticulate, rugulate, and rugulate-perforate in polar view and striate-rugulate, striate-reticulate, rugulate, and verrucate in equatorial view in exine ornamentation.…”
Section: Discussionmentioning
confidence: 56%
“…Pollen ornamentation is one of the most significant characteristics that can be used to separate taxa (Pınar et al, 2009;Mačukanović-Jocić et al, 2017;Zhang et al, 2017). We observed that Scaligeria was striate, striate-rugulate, striate-reticulate, rugulate, and rugulate-perforate in polar view and striate-rugulate, striate-reticulate, rugulate, and verrucate in equatorial view in exine ornamentation.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have used microsatellite markers to assess a broad range of genetic diversity resources in Malus germplasm collections [ 18 ]. Additionally, in morphological and biochemical diversity analyses from the parts of Malus species, phylogenetic relationships have been conducted, however, the number of them is limited [ 19 , 20 , 21 ]. However, the taxonomy of the Malus genus is complex and unclear, and in light of new genomic resources, in need of revision [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pollen grains of S. thaipingensis with higher apocolpium space is advanced though that of S. declinata is higher because S. declinata produce heteropolar pollen grains. Ornamentation pattern of pollen surface is important in the study of plant evolution and systematic taxonomy [33]. According to the concept of evolution of pollen grains stated by Yang et al [34], it can be found that the surface morphology of pollen of S. asoca having the reticulate type of exine is primitive among all.…”
Section: Discussionmentioning
confidence: 99%